From the “3D model” to the “3D scene”. Prospects and opportunities for the enhancement of an architectural and urban cultural heritage. - Ippoliti, Elena; Meschini, Alessandra (DISEGNARECON, 2010)
Multimediality is composed of “audiovisual richness, cognitive and instructive depth, interactivity”[i] and a multimedia product should be “intense, profound and versatile, riveting like a film, methodical like a book and interactive like a videogame”[ii]. With these definitions as a starting point, the proposed paper aims at investigating the possibility of increasing the awareness of our cultural heritage and spreading that knowledge using the latest technological innovations. Particular attention is given to the “3D digital scene” with reference to architectural and urban cultural heritage, as it is an excellent means of giving access to the cultural content as well as being a hub for collecting information. This approach, founded on sensorial and emotional involvement, is in effect of added value for communication, and for the elaboration and development of information and content. This makes it an extremely valid tool for the enhancement of our cultural heritage. [i] Negroponte N., Essere digitali, Sperling & Kupfer, Milano, 2004. [ii] Maragliano R., Manuale di didattica multimediale, Laterza, Roma-Bari, 1994. p.43.